2019
DOI: 10.1097/cce.0000000000000031
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Response and Cardiac Arrest Teams: A Descriptive Analysis of 103 American Hospitals

Abstract: Objectives: Despite improvements in the management of in-hospital cardiac arrest over the past decade, in-hospital cardiac arrest continues to be associated with poor prognosis. This has led to the development of rapid response systems, hospital-wide efforts to improve patient outcomes by centering on prompt identification of decompensating patients, expert clinical management, and continuous quality improvement of processes of care. The rapid response system may include cardiac arrest teams, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…Jones et al confirmed that the RRT reduces the rate of cardiac arrest and reported that one cardiac arrest could be prevented in every 17 by RRT [ 29 ]. The study found the rate of cardiac arrest decreased from 72.62 to 39.01%, which consistent with others [ 14 , 22 , 23 , 27 , 28 ]. These findings may be related to the activation criteria that can be monitored in real time, which can guide callers in identifying high-risk patients early and activate the nurse-led RRS for intervention.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Jones et al confirmed that the RRT reduces the rate of cardiac arrest and reported that one cardiac arrest could be prevented in every 17 by RRT [ 29 ]. The study found the rate of cardiac arrest decreased from 72.62 to 39.01%, which consistent with others [ 14 , 22 , 23 , 27 , 28 ]. These findings may be related to the activation criteria that can be monitored in real time, which can guide callers in identifying high-risk patients early and activate the nurse-led RRS for intervention.…”
Section: Discussionsupporting
confidence: 91%
“…Sudden cardiac arrest is a rapidly progressing event that affects millions of people every year. It is estimated that tens of thousands of people die from cardiac arrest every year, accounting for 15 to 20% of all deaths worldwide [ 22 , 23 ]. However, only a very few patients can be successfully rescued.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its widespread adoption, rapid response systems (RRS) and rapid response teams (RRT) vary significantly in composition and set-up. [1][2][3] While implementation of RRSs appear to be associated with reduced cardiac arrest rate and improved mortality, 4,5 their optimal composition, activation criteria and how they should be evaluated, remain controversial. [6][7][8][9] It is likely that RRS staffing, calling criteria and clinical pathways are influenced by the available expertise, patient case-mix and resources in each hospital.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially pertinent given the wide variation in emergency team structure in the United States. 12 The second round of the survey also had a lower response rate than the first, which may further impact the generalizability of our findings. Additionally, we only captured adaptations that had been made at the time of the initial survey, which took place during the initial wave of COVID-19 in the United States and not subsequent adaptations to team structure or function.…”
Section: Discussionmentioning
confidence: 90%